Implementation of Halal Product Assurance System on Traditional Cakes at UMKM XYZ Gowa Regency - Putra, Trisno Wardy; Sapa, Nasrullah Bin; Muthiadin, Cut (Jurnal Iqtisaduna, 2025)
This study aims to analyze the implementation of the Halal Product Assurance System (SJPH) in traditional cake products at MSME XYZ in Gowa Regency. MSMEs play a crucial role in supporting the halal economy; however, the implementation is often hindered by a lack of resources and awareness of the importance of halal certification. The method used in this research is qualitative, which aims to describe, uncover meanings, and provide in-depth explanations of the phenomenon being studied. Data collection was conducted through observation, interviews, and documentation studies. Data analysis techniques include data categorization, pattern identification, and consistency evaluation to produce comprehensive and accountable findings. The research results indicate that MSME XYZ faces several main challenges, such as the absence of halal policies, supporting documents for certain raw materials, and oversight mechanisms through audits. Nevertheless, the business owners demonstrate a strong commitment to maintaining product halalness by using raw materials that are mostly halal-certified. This study recommends the implementation of periodic audits, strengthening raw material management, and providing training for MSME actors to improve compliance with halal principles.